2021
DOI: 10.2196/28337
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19–Related Restrictions on Social and Daily Activities of Parents, People With Disabilities, and Older Adults: Protocol for a Longitudinal, Mixed Methods Study

Abstract: Background The COVID-19 pandemic has led to wide-scale changes in societal organization. This has dramatically altered people’s daily activities, especially among families with young children, those living with disabilities such as spinal cord injury (SCI), those who have experienced a stroke, and older adults. Objective We aim to (1) investigate how COVID-19 restrictions influence daily activities, (2) track the psychosocial effects of these restrictio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…This 10-month longitudinal qualitative study drew on data from a larger project on the experiences of various populations (families, people with disabilities) during the pandemic ( Reid et al, 2021 ). The local ethics board approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…This 10-month longitudinal qualitative study drew on data from a larger project on the experiences of various populations (families, people with disabilities) during the pandemic ( Reid et al, 2021 ). The local ethics board approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…This study is part of a larger study exploring COVID-19 experiences across a range of populations, including disabilities and families ( 13 ). This study used an interpretive phenomenological methodology ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
“…First, future study may wish to examine longitudinal studies on how the mental health of a vulnerable group has changed throughout the COVID-19 era. For example, recently protocols of studies investigating the longitudinal impact of COVID-19 on the mental health of people with disabilities, the elderly [83], and pregnant women and their children [84] have been published. Second, the use of clinicians' standardized assessments other than self-reported measures can be suggested for future studies, by which the prevalence of diagnosed psychiatric disorders can be better confirmed.…”
Section: Suggestion Of Future Studiesmentioning
confidence: 99%